Considerations on Safety Parameters, Product Quality and Process Reliability for the Usage of Microwaves and Plasma Torch Burners in High-Temperature Processes - Ralph Behend; Dominik Liebsch; Andreas Pestel; Hartmut Krause; Sven Eckart (Chemical Engineering Transactions, 2025)
Microwave plasma offers several advantages across various industrial applications. It enables highly efficient and targeted energy transfer to materials, resulting in lower energy consumption compared to conventional high-temperature processes such as liquid and gaseous burners. The controllability of microwave plasmas allows for precise control of high-temperature processes, leading to improved product quality and reproducibility. Nevertheless, the utilization of microwaves and microwave plasmas in industrial process systems presents various potential risks that need to be carefully considered. This manuscript outlines the primary risks and challenges during the implementation and operation in high temperature processes. Microwave radiation can pose health hazards, particularly if handled improperly or without adequate shielding. Humans exposed to such conditions may suffer from tissue damage, eye irritation, and impairments to the nervous system. Further, microwave generation has the potential to generate electromagnetic interference, which can disrupt or damage sensitive electronic equipment. To safeguard against such interference, effective shielding measures are essential. Additionally, environmental considerations surrounding microwave plasma usage are also significant. Depending on the particular process employed, there is a possibility of releasing pollutants such as large concentration of ozone and nitrogen oxides into the environment. Microwave plasmas present significant explosion and fire risks, particularly in environments where flammable gases or dust are present. The interaction between the plasma and these combustible materials can lead to dangerous incidents. To mitigate these dangers effectively, it is crucial to implement stringent safety measures, including proper monitoring, containment, and control systems, to ensure a safe operating environment. Some of the available techniques will be summarized. The high temperatures and reactive species produced in microwave plasmas can lead to significant material degradation. Components directly exposed to the plasma are especially vulnerable, often experiencing corrosion or erosion. This can compromise the integrity and longevity of the materials, necessitating careful selection of materials especially in combination with high wall temperatures. These risks can be effectively managed through thorough risk assessments, robust safety protocols, adequate protective measures, and regular maintenance. The benefits of using microwaves and microwave plasmas, such as high energy efficiency and precise process control, support their application in many industrial settings.